An audit of transfusion reaction monitoring and reporting at a cancer hospital in Pakistan- a step towards hemovigilance - Muhammad Hasan; Imran Ahmed Siddiqui; Zahid Qamar; Asad Hayat (Journal of the Pakistan Medical Association, 2020)
Objective: To monitor the frequencies of different adverse transfusion reactions and to assess the compliance of clinical staff with the process of sending proper transfusion reaction workup within the specified time. Methods: The retrospective audit was conducted at the blood bank of Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised all transfusion reaction forms received from July 1, 2017, to June 30, 2018. The forms were analysed for type of blood component, time in which it was received by thw blood bank, whether or not the form was completely filled, whether or not all required samples were provided, and the type of reaction. Results: Of the 12,787 units dispensed and transfused, 50(0.39%) transfusion reactions were noted. Allergic was the most frequent type 24(48%). Red cells accounted for 38(76%) of the reactions. In 58(95%) cases, reaction forms were completely filled. Blood bags in 36(59%) and post-transfusion ethylenediaminetetraacetic acid samples in 35(57.3%) cases were received at blood bank within 2 hours of reaction. Conclusion: Incidence of transfusion reactions was found to be low as there was good compliance with procedures on the part of the clinical staff. Key Words: Transfusion reactions, Haemo-vigilance, Clinical audit.